EFFECTIVENESS OF PROPER NUTRITION IN GOUT (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Gout is a common inflammatory arthritis characterized by the accumulation of uric acid crystals in the joints, which leads to severe pain and discomfort. This article explores the effects of proper nutrition on managing and preventing gout. The analysis shows that specific nutrition strategies can effectively lower uric acid levels, reduce flare-ups, and improve the health of people with gout.